Aral teńizÍ boyÍ BalÍqshÍlÍq kásibine baylanÍslÍ leksika - Quttımuratova, Í.A. (SCIENCE and SOCIETY, 2024)
The article deals with professionalisms connected with fishing in the language of the Kazakh people in Muinak and Kungrad regions of Karakalpakstan. The problem of study of various dialects of the Kazakh language in the lingua-geographic aspect is still the most current one. This circumstance allows the researches to admit a big significance of study of the lexical dialectology of the Kazakhs inhabiting the Kungrad area by the lingua-geographic method.